Tax literacy among employees: Sabah and Sarawaks perspective - Madi, Nero; Kamaluddin, Amrizah; Janggu, Tamoi; Ibrahim, Muliati Aba; Abu Samah, Aizimah; Jusoff, Kamaruzaman (Canadian Center of Science and Education, 2010)
The main intent of this paper is to gauge the level of tax literacy among taxpayers in Sabah and Sarawak. It is vital to shed light on our preparation to face the challenge posed by the implementation of Self -Assessment System (SAS) in 2004 whereby the taxpayers are expected to be functionally tax-literate in computing their own tax liabilities accurately. Methodologically, the subjects were randomly sampled from taxpayers working in a few selected towns in Sarawak and Sabah. Statistical tests like t-tests and chi-square were applied onto the means of tax literacy scores by each state and the taxpayers’ respective workplaces. The taxpayers in Sarawak were found to be more tax-literate as compared to their counterparts in Sabah. Nonetheless, the taxpayers in both states were not eventually prepared for SAS. More aggressive efforts were recommended to raise the level of tax literacy among the taxpayers.